2020
DOI: 10.1371/journal.pone.0239029
|View full text |Cite
|
Sign up to set email alerts
|

Do bank voles (Myodes glareolus) trapped in live and lethal traps show differences in tick burden?

Abstract: In studies assessing tick abundance, the use of live traps to capture and euthanize rodent hosts is a commonly used method to determine their burden. However, captive animals can experience debilitating or fatal capture stress as a result prior to collection. An alternative method is the use of lethal traps, but this can potentially lead to tick drop-off between the time of capture and collection. In this study, in order to determine whether subjecting animals to capture stress is inevitable, we tested the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Lethal traps were baited with peanut butter for practical reasons as it is easily applied to the inside of the trap body. Trap type does not influence tick burden size on the captured animals [ 60 ]. At each altitude, the live and lethal plots were placed at approximately 100 m distance from each other, but in locations with similar vegetation structure and habitat characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Lethal traps were baited with peanut butter for practical reasons as it is easily applied to the inside of the trap body. Trap type does not influence tick burden size on the captured animals [ 60 ]. At each altitude, the live and lethal plots were placed at approximately 100 m distance from each other, but in locations with similar vegetation structure and habitat characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…3). These two trap types had no measurable impact on tick infestation in a study on this specific topic (De Pelsmaeker et al 2020 ), and we found no measurable effects of whether the animal was found alive or dead in a supporting analysis detailed in the appendices (Table S6). Each of the four trap stations at each trapping site consisted of either 1 cage trap or 3 snap traps (to avoid trap saturation) in a triangle formation.…”
Section: Methodsmentioning
confidence: 47%
“…The other plot was equipped with lethal traps (Rapp2 Mousetrap, http://www.rappfellene.no), and baited with peanut butter. A previous study has shown that both trap types perform similarily in terms of trapping efficiency and tick burdens (De Pelsmaeker et al, 2020). Humidity and temperature were recorded at station level every hour for the duration of the trapping period, using a TinyTag Plus 2 – TGP 4017 datalogger, housed in a DataMate instrument cover ACS‐5050, mounted approximately 50 cm aboveground level.…”
Section: Methodsmentioning
confidence: 86%